Eficiência técnica das gestões municipais de educação no Estado do Ceará - Falcão, Elizabeth Barbosa de Melo (2017)
This article uses a three-stage approach to measure and evaluate the efficiency of municipal management of basic education in the state of Ceará in the period of 2015. The DEA-SBM method was applied and a transformation was applied in the efficiency scores to control the impacts of variables not discretionary. The results indicate a high concentration of relatively inefficient municipalities with low efficacy, identifying a problem of allocation of existing resources. In the third stage, the finite mix model identified the presence of heterogeneity along the distribution of managerial efficiency. We found the presence of economies of scale for the tails of distribution and asymmetry in the impact of party-political rotation on different scales of efficiency.